Cover Picture: Insights into TIM‐Barrel Prenyl Transferase Mechanisms: Crystal Structures of PcrB from Bacillus subtilis and Staphylococcus aureus (ChemBioChem 2/2013). Issue 2 (17th January 2013) - Ren, Feifei; Feng, Xinxin; Ko, Tzu‐Ping; Huang, Chun‐Hsiang; Hu, Yumei; Chan, Hsiu‐Chien; Liu, Yi‐Liang; Wang, Ke; Chen, Chun‐Chi; Pang, Xuefei; He, Miao; Li, Yujie; et al.
<x xml:space="preserve">Abstract</x> The cover picture shows the structure of the prenyl transferase PcrB. Prenyl transferases (PTs) play a key role in isoprenoid biosynthesis, and recently a new group of PTs with a triose phosphate isomerase (TIM)‐barrel fold have been discovered. The structures of PcrB from Bacillus subtilis and Staphylococcus aureus are reported here and show that there are two tyrosines and one glutamic acid in the active‐site region that are poised to activate the substrate's C3 OH group for nucleophilic attack, as well as remove H+ from the active‐site region. The position of the prenyl diphosphate, which binds to an essential aspartic acid via Mg2+, was also located, and by using bioinformatics and site‐directed mutagenesis, a role for another tyrosine residue, in chain elongation, was demonstrated. In the article on p. 195 ff., E. Oldfield, R.‐T. Guo et al. show how the results also provide a structural basis for the binding of a highly bent isoprenoid side chain in another TIM barrel PT, MoeO5.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>